Lactogenic effects of traditional cereal-based diets on neonatal development in Wistar rat: Impacts of Indigenous Grains on Lactation and Pup Growth Outcomes - Oyelowo, Oluwakemi; Unuigbe, Joy (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: This study evaluated the effects of maternal consumption of five natural galactagogues: Zea mays, Eleusine coracana, Panicum miliaceum, and Pennisetum glaucum on growth and metabolic outcomes in suckling Wistar rat pups. METHODOLOGY: Sixty pregnant Wistar rats were allowed to deliver. After parturition, the dams were randomly assigned to control and experimental groups and were all given normal rat chow and water. Besides that, the dams in the experimental groups received 100g/kg/day of yellow Zea mays, white Zea mays, Pennisetum glaucum, Eleusine coracana, and Panicum miliaceum respectively and a group was also administered metoclopramide (5mg/kg/day), a pharmacological galactagogue. The administrations began from postnatal day 2 (PND 2) and lasted the period of lactation. Developmental milestones were tracked, and lipid and protein profiles were analyzed in brain, serum, and liver samples from male and female pups using GraphPad Prism, with results expressed as mean ± SD. RESULTS: Results showed that all cereal diets affected developmental milestones, milk yield and body weight, with Eleusine coracana, yellow Zea mays, and Pennisetum glaucum demonstrating particularly notable improvements in lactation, lipid metabolism, and protein synthesis. CONCLUSION: In conclusion, cereal preparations from Zea mays, Eleusine coracana, Panicum miliaceum, and Pennisetum glaucum enhanced lactation, improved infant growth, and influenced metabolism. Notably, Eleusine coracana, Yellow Zea mays, and Pennisetum glaucum emerged as the most impactful in these areas.